2006
DOI: 10.1271/bbb.70.1013
|View full text |Cite
|
Sign up to set email alerts
|

Specific Characteristics of Family 45 Endoglucanases from Mucorales in the Use of Textiles and Laundry

Abstract: We examined the characteristics of family 45 endoglucanases (glycoside hydrolases family 45; GH45) from Mucorales belonging to Zygomycota in the use of textiles and laundry. The defibrillation activities on lyocell fabric of family 45 endoglucanases from Mucorales, such as RCE1 and RCE2 from Rhizopus oryzae, MCE1 and MCE2 from Mucor circinelloides, and PCE1 from Phycomyces nitens, were much higher than those of the other family 45 endoglucanases. By contrast, family 45 endoglucanases from Mucorales were less r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…These properties are similar to those of cellulases from thermophilic fungi (Maheshwari et al 2000), and are of special interest as stable enzymes are required for industrial processes (Bhat 2000). The analysis of stability in alkaline conditions showed that most of the enzymes produced (CMCase bands of 65-67, 61 and 42 kDa) are alkali-resistant cellulases, which remained stable at pH 9 and 65°C for at least 1 h. Cellulases that are active and stable at high temperatures and alkaline pH are of special interest in the detergency industry, where enzymes and detergent additives must be active in harsh washing conditions (Wang et al 2005;Simonaka et al 2006). In paper recycling, cellulases can be applied to facilitate deinking in the flotation cells, which usually operate under alkaline and high temperature conditions (Bajpai and Bajpai 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These properties are similar to those of cellulases from thermophilic fungi (Maheshwari et al 2000), and are of special interest as stable enzymes are required for industrial processes (Bhat 2000). The analysis of stability in alkaline conditions showed that most of the enzymes produced (CMCase bands of 65-67, 61 and 42 kDa) are alkali-resistant cellulases, which remained stable at pH 9 and 65°C for at least 1 h. Cellulases that are active and stable at high temperatures and alkaline pH are of special interest in the detergency industry, where enzymes and detergent additives must be active in harsh washing conditions (Wang et al 2005;Simonaka et al 2006). In paper recycling, cellulases can be applied to facilitate deinking in the flotation cells, which usually operate under alkaline and high temperature conditions (Bajpai and Bajpai 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Endoglucanases produced by zygomycetes in liquid medium containing chitin or wheat bran, have been investigated and compared to commercial endoglucanases. Potential applications for endoglucanases appear in the brewery industry, where these enzymes lead to lower viscosity (Celestino et al, 2006), and in the textile industry, where they induce higher defibrillation activities on lyocell fabric as well as lower resistance to anionic surfactants and oxidizing agents (Shimonaka et al, 2006). In the animal feed industry, the enzymes showed higher thermostability and activity at pH 2.6-6.5 than current commercialized β-glucanases ( Rhizopus microsporus by employing solid-state fermentation, based on wheat bran, straw, and grain sprouts, and also submerged fermentation, based on xylose, maize extract, and salts.…”
Section: Cellulases and Related Enzymesmentioning
confidence: 99%
“…Based on the results on May 9, 2018 by guest http://aem.asm.org/ described here, STCE1 is considered to be an all-around suitable enzyme that has all the properties required for laundry use. Although the catalytic domain of RCE1 had high defibrillation activities on dyed cotton and lyocell fabrics, this enzyme had low resistance to anionic surfactants and oxidizing agents (29,35). By contrast, the catalytic domain of EGL3 was highly resistant to anionic surfactants and oxidizing agents, whereas it had low defibrillation activity on dyed lyocell fabrics (35).…”
Section: Resultsmentioning
confidence: 99%
“…Although the catalytic domain of RCE1 had high defibrillation activities on dyed cotton and lyocell fabrics, this enzyme had low resistance to anionic surfactants and oxidizing agents (29,35). By contrast, the catalytic domain of EGL3 was highly resistant to anionic surfactants and oxidizing agents, whereas it had low defibrillation activity on dyed lyocell fabrics (35). In a previous study, to identify the amino acids involved in the various properties needed for laundering, we compared the characteristics of RCE1, EGL3, and three chimeric enzymes (ER1, ER2, and ER3) in which each of the three regions of the catalytic domain of EGL3 was replaced with the corresponding region of the catalytic domain of RCE1 (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation